Effectiveness of the Covid-19 Module in Preventing and Reducing the Positive Rate of Covid-19 during the New Normal Period in the City of Padang. - Asep Irfan; Darwel Darwel; Suksmerri Suksmerri; Delima Delima; Sari Arlinda (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Although the number of people exposed to COVID-19 in Indonesia is currently under control, efforts to prevent COVID-19 must still be carried out properly to avoid the dangers of COVID-19 which are always threatening. The study aimed to determine community participation in the Prevention and Reduction of the Positive Rate of Covid 19 during the New Adaptation Period. This type of research is quantitative with a cross-sectional study design. The research was conducted in the city of Padang. The intervention was implemented by implementing the Corona Virus Disease 19 (Covid-19) module on the Prevention of Covid 19 Disease Behavior in the City of Padang. The sampling technique used was purposive sampling, with as many as 123 people. Data were analyzed by univariate and bivariate, with statistical test dependent t / paired t. The results of the study: the average score of Covid prevention measures before being given an intervention was 47.6098 and after receiving an intervention it increased to 52.6992. The analysis showed that with the value of p = 0.000 (p less than 0.05), there was a significant difference in community participation in efforts to prevent copying. To prevent Covid 19, it is necessary always to carry out promotive and preventive efforts, one method of providing education can be used, one of which is through interactive media in the form of educational videos and educational modules. Abstrak: Meski jumlah orang yang terpapar COVID-19 di Indonesia saat ini sudah terkendali, namun upaya pencegahan COVID-19 tetap harus dilakukan dengan baik untuk menghindari bahaya COVID-19 yang selalu mengancam. Tujuan penelitian adalah mengetahui partisipasi masyarakat dalam Pencegahan Dan Penurunan Angka Positif Rate Covid 19 Pada Masa Adaptasi Baru.  Jenis penelitian ini kuantitatif dengan desain crossectional studi. Penelitian dilakukan di Kota Padang. Intervensi yang dilakukan penerapan modul Corona Virus Desease 19 (Covid-19) Terhadap Perilaku Pencegahan Penyakit Covid 19 di Kota Padang Teknik sampling yang digunakan purposive sampling, sebanyak 123 orang. Data dianalisis dengan univariat dan bivariat, dengan uji statistik t dependen/ paired t. Hasil penelitian: rata rata skort tindakan pencehgehan Covid sebelum diberi intervensi 47.6098 dan setelah mendapat intervensi meningkat menjadi 52.6992. Hasil analisis didapatka nilai p=0,000 (p kurang dari 0,05) terdapat perbedaan yang signifikan partisipasi masyarakat dalam upaya pencegahan copid. Untuk mencegah Covid 19, perlu upaya promotif dan preventif yang selalu dilakukan, salah satu metode penyelenggaraan pendidikan dapat digunakan, salah satunya melalui media interaktif berupa video edukasi maupun modul edukasi.